Is Intra-Articular Magnesium Effective for Postoperative Analgesia in Arthroscopic Shoulder Surgery? - Tuba Berra Saritas; Hale Borazan; Selmin Okesli; Mustafa Yel; Seref Otelcioglu (Pain Research and Management)
BACKGROUND: Various medications are used intra-articularly for postoperative pain reduction after arthroscopic shoulder surgery. Magnesium, a N-methyl-D-aspartate receptor antagonist, may be effective for reduction of both postoperative pain scores and analgesic requirements.